The Autism Phenome Project: Toward Identifying Clinically Meaningful Subgroups of Autism - Nordahl, Christine Wu; Andrews, Derek Sayre; Dwyer, Patrick; Waizbard-Bartov, Einat; Restrepo, Bibiana; Lee, Joshua K.; Heath, Brianna; Saron, Clifford; Rivera, Susan M.; Solomon, Marjorie; Ashwood, Paul; Amaral, David G. (Frontiers in Neuroscience, 2022)
One of the most universally accepted facts about autism is that it is heterogenous. Individuals diagnosed with autism spectrum disorder have a wide range of behavioral presentations and a variety of co-occurring medical and mental health conditions. The identification of more homogenous subgroups is likely to lead to a better understanding of etiologies as well as more targeted interventions and treatments. In 2006, we initiated the UC Davis MIND Institute Autism Phenome Project (APP) with the overarching goal of identifying clinically meaningful subtypes of autism. This ongoing longitudinal multidisciplinary study now includes over 400 children and involves comprehensive medical, behavioral, and neuroimaging assessments from early childhood through adolescence (2 to 19 years of age). We have employed several strategies to identify sub-populations within autistic individuals: subgrouping by neural, biological, behavioral or clinical characteristics as well as by developmental trajectories. In this Mini Review, we summarize findings to date from the APP cohort and describe progress made towards identifying meaningful subgroups of autism.